DESAIN PENGEMBANGAN MANDALA SAND SEBAGAI MEDIA SENI RUPA KELAS IV DI SEKOLAH DASAR - Dewi Rona Sofiyani; Rofian; Prasena Arisyanto (STKIP Subang, 2024)
In the background of this research, teachers have not used learning media and are still using minimal media, namely in the form of LKS books. This research aims to explain the development of Mandala Sand media in grade IV elementary school fine arts learning. The researcher used the type of R&D research and development using Sugiyono's book which was carried out up to step 6, the steps are as follows; (1) Potential and problems; (2) Data collection; (3) Product design; (4) Design validation; (5) Design revision; and (6) Product testing. The results of material expert validation obtained a percentage of 100% with the criteria